SME policy index : Western Balkans and Turkey 2012 : progress in the implementation of the Small Business Act for Europe - Organisation for Economic Co-operation and Development; European Commission; European Training Foundation; European Bank for Reconstruction and Development (OECD, 2012)
Summary.
Keywords: pienyritykset; yrittäjyys; pk-yritykset; pk-yritykset : Albania; pk-yritykset : Bosnia-Hertsegovina; pk-yritykset : Kroatia; pk-yritykset : Kosovo; pk-yritykset : Makedonia; pk-yritykset : Montenegro; pk-yritykset : Serbia; pk-yritykset : Turkki